1973
DOI: 10.2466/pms.1973.36.3.835
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Intimacy, Physical Distance and Eye Contact

Abstract: S~zmmasy.-30 male Ss rated photographic slides on the degree of intimacy of 2 males shown seated at a cafeteria table. Another 10 Ss rated the slides on both intimacy and eye contact. 54 different seating arrangements were used. Side and corner arrangements were varied by body and head position through 5 angles (On, 30°, 45O, 60°, 90") and 3 distances (3, 4.5, 6 ft.). Results supported the main hypotheses that intimacy varies inversely with distance, that intimacy ratings are directly related to ratings of eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 7 publications
(6 reference statements)
0
15
0
Order By: Relevance
“…However, mutual gaze transmits information above and beyond linguistic regulation. Research demonstrates that people who exhibit high levels of mutual gaze are perceived as intimate (Scherer & Schiff, 1973), attentive (Breed, Christiansen, & Larson, 1972), competent (Sodikoff, Firestone, & Kaplan, 1974), and powerful (Argyle, Lefebvre, & Cook, 1974). In addition, people can be inuenced by mutual gaze without necessarily being aware of it (Zajonc, 1980).…”
Section: Mutual Gazementioning
confidence: 95%
“…However, mutual gaze transmits information above and beyond linguistic regulation. Research demonstrates that people who exhibit high levels of mutual gaze are perceived as intimate (Scherer & Schiff, 1973), attentive (Breed, Christiansen, & Larson, 1972), competent (Sodikoff, Firestone, & Kaplan, 1974), and powerful (Argyle, Lefebvre, & Cook, 1974). In addition, people can be inuenced by mutual gaze without necessarily being aware of it (Zajonc, 1980).…”
Section: Mutual Gazementioning
confidence: 95%
“…Little research has examined the nonverbal cues that correspond to increases in such arousal. However, if nonverbal indicators of intimacy, attraction, liking, and similarity can be taken as possible signals of attraction-based arousal, then positively valenced arousal should be evidenced by increased involvement and affiliation cues, such as more gaze time, forward lean, close proximity, smiling, touch, postural attentiveness, gestural animation, vocal animation, faster tempo, shorter pauses and response latencies, and vocal warmth (Burgoon, Buller, Hale, & deTurck, 1984;Byrne, Ervin, & Lamberth, 1970;Coker & Burgoon, 1987;Scherer & Schiff, 1973;Siegman, 1978Siegman, , 1979. High social arousal may also be accompanied by natural laughter, which may serve as an arousal release mechanism (Chapman, 1975).…”
Section: Proxemic Invasionsmentioning
confidence: 99%
“…Many studies have shown that gaze behaviors are related to a person’s likeability. For example, studies have shown that people in photographs and videotapes are rated as liking each other more when they share high levels of gaze (Kleinke, Meeker, & Fong, 1974; Mehrabian, 1968; Naiman & Breed, 1974; Scherer & Schiff, 1973; Thayer & Schiff, 1974). Researchers have also found that gaze influences people’s liking for each other; specifically in moderation, as study participants preferred people who provided moderate amounts of gaze over constant or no gaze (Argyle, Lefebvre, & Cook, 1974).…”
Section: Introductionmentioning
confidence: 99%